The child with haemophilia - C. D. Karabus (AOSIS, 1981)
Haemophilias are bleeding disorders due to an inherited defect in production of clotting factors. In South Africa 867 haemophiliacs have been registered and 309 of these are boys under 15 years of age. Haemophilia A and B make up about 85-90% of all cases. They are inherited in a sex-linked manner and thus affect males only. The manifestations of haemophilia are due to bleeding characteristically involving the joints. The disorder varies in severity and in the most severely affected children, repeated hemarthroses may lead to crippling. Early administration of clotting factor, preferably given at the child's home, physiotherapy to prevent muscle wasting and regular assessment by a co-ordinated team of paediatrician, physiotherapist, orthopaedic surgeon and dentist at the hospital are necessary for successful management. These facilities can be organised only at a comprehensive haemophilia treatment centre treating a large number of bleeders.